PEMBUATAN SELAI LEMBARAN DARI ALBEDO SEMANGKA DAN TERONG BELANDA - Megawati Megawati; Vonny Setiaries Johan; Yusmarini Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to get the best formulation of sliced jam from watermelon’s albedo and tamarillo. The research used a Complete Randomized Design (CRD) with four treatments and four replications. The treatments were AT1 (watermelon’s albedo pulp 90% and tamarillo pulp 10%), AT2 (watermelon’s albedo pulp 70% and tamarillo pulp 30%), AT3 (watermelon’s albedo pulp 50% and tamarillo pulp 50%), and AT4 (watermelon’s albedo pulp 30% and tamarillo pulp 70%). The data analyzed statistically using Anova and DNMRT at 5%. The research showed that the combination of watermelon’s albedo and tamarillo significantly effect on moisture content, ash content, degree of acidity (pH), pectin content, reducing sugar content, total dissolved solids, colour, taste, flavor, texture, and hedonic test. Sliced jam elected from this study was the sliced jam treatment AT4 with ratio watermelon’s albedo 30% and tamarillo 70% which has moisture content (26.33%), ash content (0.97%), degree of acidity (3.60), pectin content (2.09%), reducing sugar content (20.23%), total dissolved solids (65.10°brix), red colour, tamarillo flavor, sweet little sour taste, the texture was little chewy and panelist like the sliced jam at overall assessment. Keywords: sliced jam, watermelon’s albedo, and tamarillo.